Kondisi Tata Air Sungai Dalam Pengelolaan Daerah Aliran Sungai Di Sub DAS Rokan Kiri - Siahaan, Haryanto; Handayani, Yohanna Lilis; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Watersheds management can be evaluated by the criteria of its preservation. The main criteria of watershed`s preservation is the environment goodness which lies on land use, water system, social, economy, and institutions. The criteria of stream system can be scored from several indicators, such as : stream`s regim coefficient, coefficient of variation, water utilization index, and runoff coefficient. This research aimed to find out the classification result from the reviewed parameters on Rokan Kiri Sub Watershed based on rules by Peraturan Direktur Jenderal Rehabilitasi Lahan dan Perhutanan Sosial No. P.04/V-SET/2009. On this research, it has been done the analysis steps and the computation about stream system`s criteria by stream`s discharge indicators. The result of this research has shown that stream system`s condition with indicator of stream`s regim coefficient valued 223,92 which placed on low class, indicator of variation coefficient valued 0,73 which placed on low class, indicator of water usement index scored 0,0035 which placed on well class, and coefficient runoff valued 0,27 which placed on medium class.Keywords : Stream System, Stream`s regim coefficient, Coefficient of Variation, Water utilization Index, Runoff Coefficient.